Pengaruh Manajemen Aset, Kinerja Lingkungan dan Struktur Modal terhadap Kinerja Keuangan - Sianturi, Lasmaria Trianti; Purwatiningsih, Purwatiningsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to analyze the asset management, environmental performance, capital structure on financial performance in energy sector companies listed on the IDX for the 2018-2022 period. The total research population was 73 samples taken from 7 energy sector companies over a 5 year period energy companies listed on the IDX using a purposive sampling method. Research data was analyzed using panel data regression analysis. This research obtained using Eviews 12 shows that the simultaneous variables of asset management, environmental performance, capital structure have a significant effect on financial performance. Partially, aset management have a significant effect on financial performance, environmental performance has no a significant effect on financial performance, and capital structure has no a significant effect on financial performance.